BENTHIC DIATOM COMMUNITIES AND ITS RELATIONSHIP TO WATER QUALITY OF THE DAY - NHUE RIVERS - Thuỷ, Dương Thị; Kiên, Hoàng Trung; Nguyệt, Vũ Thị; Phương Quỳnh, Lê Thị; Kim, Đặng Đình (Vietnam Journal of Science and Technology, 2012)
SUMMARYWater and benthic diatom communities were collected at 6 sampling stations in Nhue and Day rivers.  A total of 183 diatom taxa belonging 7 famillies were found in Nhue - Day river system. These were mainly cosmopolitan taxa, with some tropical, subtropical and endemic taxa. Environmental variables and diatom assemblage composition at all sites were significantly correlated. Water quality and diatom communities of Nhue and Day rivers were classified into 3 groups. The most abundant taxa at upstream of Day river were Achnanthidium minutissimum, Cymbella affinis. Diatom communities at Mai Linh and Khe Tang were characterized by polluted taxa such as Cyclotella meneghiniana, Nitzschia palea, Gomphonema parvulum.